Assessment of the state of machine-building industry in Ukraine - Kyrylenko, Liana; Shmyholʹ, Nadiya (Technology audit and production reserves, 2017)
The object of research is the machine-building industry of Ukraine, which is one of the most important industries of Ukraine. One of the most problematic areas is the reduction in the volume of production and sales of products, the decrease in sales markets due to the crisis state of the country. It is proposed to use diagnostics and monitoring tools to assess the activities of machine-building industry enterprises, which will allow to identify «bottlenecks» in a timely manner. Thanks to the use of diagnostic and monitoring tools, enterprises can continuously analyze the methods used to improve the condition, and conduct observations of the results. The evaluation of the performance of machine-building in the Zaporizhzhia region was carried out. According to the calculated data, it can be said that the engineering industry of the Zaporizhzhia region is gradually gaining momentum in the production and sale of manufactured products. But since 2013, there has been a slight decline in the exports of machine-building products and of Ukraine in general and machine-building enterprises in the Zaporizhzhia region in particular. The prices of the Zaporizhzhia region as one of the ways to improve the state of the machine-building industry is creation of joint ventures with foreign partners and increase investment attractiveness, because there are all conditions for efficient and profitable operation of industrial enterprises. Due to the evaluation of the performance indicators of machine-building in the Zaporizhzhia region, factors that inhibit the development of Ukrainian machine-building enterprises are identified, including the lack of high-tech industries, outdated management methods, low level of innovation and investment attractiveness. To overcome these negative factors and for the successful development of the industry, it is necessary to maintain the competitiveness of products on the global and domestic markets by improving the quality and reliability of the products